GRAVITY–OPERATED IMPACT FEEDER DYNAMICS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
This paper deals with the dynamics of rigid body that collide with a rigid surface; such motion with impact of bodies takes place in the gravity operated impact feeders. Feeders are mechanisms of the single- peace feeding for the forced moving of the oriented workpieces. In this work the vertical gravity-impact feeder for moving of the prismatic or plane details is presented. The parts move on inclined guiding plates, free fall and collide with the down plates, the impact phenomena may be used both for decreasing of velocity and for the orientation of the tracking workpieces (lateral reversing). System of equations of plane motion of detail, including stages of sliding on the slope guideway, free flight, impact and motion to the next guideway, are written down. System of equations is solved numerically with help of MathCAD program.